The Impact of Social Media on E-Commerce Decision Making Process - Curzi Valerio; Lecoq William; Quéré Noémier (International Journal of Technology for Business (IJTB), 2019)
The affirmation of social media platforms has radically changed customers purchasing habits and the way businesses develop their e-commerce sites. Indeed, e-vendors no longer invest money exclusively on advertisements on their e-commerce platforms; rather there is a fierce online competition among companies promoting their goods and services on social media channels. On the other hand, customers use social media to generate content and to network with other users so as they can gather and share as much information as possible about prices, product quality, customer service and e-sellers reputation. In addition, it is believed that social media facilitates social interaction among customers, leading to increased trust and intention to buy. In this article, we will point out how social media influences the e-commerce decision making by firstly reasoning on theoretical concepts about online customers behaviours along with the factors affecting their purchasing choices, and then by illustrating useful statistics which indicates how social media marketing has exponentially grown over the last decade.
Keywords: 650; Decision Making Process; Social Influence; Social Media Marketing; Trust